$$\mathrm{Find}\:\mathrm{the}\:\mathrm{regression}\:\mathrm{coefficient}\:{b}_{{xy}} \:\mathrm{between} \\$$$${x}\:\mathrm{and}\:{y}\:\mathrm{for}\:\mathrm{the}\:\mathrm{following}\:\mathrm{data}: \\$$$$\Sigma{x}=\mathrm{24},\:\Sigma{y}=\mathrm{44},\:\Sigma{xy}=\mathrm{306},\:\Sigma{x}^{\mathrm{2}} =\mathrm{164}, \\$$$$\Sigma{y}^{\mathrm{2}} =\mathrm{574}\:\mathrm{and}\:{n}=\mathrm{4}. \\$$
$$\mathrm{The}\:\mathrm{given}\:\mathrm{data}\:\mathrm{may}\:\mathrm{be}\:\mathrm{written}\:\mathrm{as} \\$$$$\Sigma{x}_{{i}} =\mathrm{24},\:\Sigma{y}_{{i}} =\mathrm{44},\:\Sigma{x}_{{i}} {y}_{{i}} =\mathrm{306},\:\Sigma{x}_{{i}} ^{\mathrm{2}} =\mathrm{164}, \\$$$$\Sigma{y}_{{i}} ^{\mathrm{2}} =\mathrm{574},\:\mathrm{and}\:{n}=\mathrm{4} \\$$$$\therefore{b}_{{yx}} =\frac{\left\{\Sigma{x}_{{i}} {y}_{{i}} −\frac{\left(\Sigma{x}_{{i}} \right)\left(\Sigma{y}_{{i}} \right)}{{n}}\right\}}{\left\{\Sigma{x}_{{i}} ^{\mathrm{2}} −\frac{\left(\Sigma{x}_{{i}} \right)^{\mathrm{2}} }{{n}}\right\}} \\$$$$=\frac{\left\{\mathrm{306}−\frac{\mathrm{24}×\mathrm{44}}{\mathrm{4}}\right\}}{\left\{\mathrm{164}−\frac{\left(\mathrm{24}\right)^{\mathrm{2}} }{\mathrm{4}}\right\}} \\$$$$=\frac{\mathrm{42}}{\mathrm{20}}=\mathrm{2}.\mathrm{1} \\$$